Culture of Retinal Pigment Epithelium from Evisceration Specimens - Han-Yi Tseng (Kaohsiung Journal of Medical Sciences, 2004)
Human retinal pigment epithelial (RPE) cell cultures are usually obtained from donor eyes; isolation and culture of RPE cells obtained by evisceration has not been reported previously. The present study attempted to isolate and cultivate RPE cells from evisceration specimens obtained from two cases with severe ocular trauma. Two different isolation methods, explantation and enzymatic dissociation, were used. In Case 1, RPE cells grew from the explants, but were contaminated with other cells such as fibroblasts and melanocytes, and no pure RPE cultures were obtained by explantation. In Case 2, RPE cells were separated from choroids using 0.25% trypsin before plating for culture, which effectively eliminated contaminating cells. A pure RPE culture was obtained and cultured with F12 medium supplemented with 30% fetal bovine serum. With this enzymatic dissociation method, cultured RPE cells grew to confluence in primary culture and could be maintained in culture for five passages. Cultured RPE cells were identified by the presence of cytokeratin expression, as shown by immunocytochemical staining. These isolation and culture methods provide alternative sources for human RPE cells and could be useful in studies of the cell biology and pathophysiology of human RPE cells.